If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 3) = 2x + -10 Reorder the terms: (2 + x)(x + 3) = 2x + -10 Reorder the terms: (2 + x)(3 + x) = 2x + -10 Multiply (2 + x) * (3 + x) (2(3 + x) + x(3 + x)) = 2x + -10 ((3 * 2 + x * 2) + x(3 + x)) = 2x + -10 ((6 + 2x) + x(3 + x)) = 2x + -10 (6 + 2x + (3 * x + x * x)) = 2x + -10 (6 + 2x + (3x + x2)) = 2x + -10 Combine like terms: 2x + 3x = 5x (6 + 5x + x2) = 2x + -10 Reorder the terms: 6 + 5x + x2 = -10 + 2x Solving 6 + 5x + x2 = -10 + 2x Solving for variable 'x'. Reorder the terms: 6 + 10 + 5x + -2x + x2 = -10 + 2x + 10 + -2x Combine like terms: 6 + 10 = 16 16 + 5x + -2x + x2 = -10 + 2x + 10 + -2x Combine like terms: 5x + -2x = 3x 16 + 3x + x2 = -10 + 2x + 10 + -2x Reorder the terms: 16 + 3x + x2 = -10 + 10 + 2x + -2x Combine like terms: -10 + 10 = 0 16 + 3x + x2 = 0 + 2x + -2x 16 + 3x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 16 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-16' to each side of the equation. 16 + 3x + -16 + x2 = 0 + -16 Reorder the terms: 16 + -16 + 3x + x2 = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 3x + x2 = 0 + -16 3x + x2 = 0 + -16 Combine like terms: 0 + -16 = -16 3x + x2 = -16 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = -16 + 2.25 Reorder the terms: 2.25 + 3x + x2 = -16 + 2.25 Combine like terms: -16 + 2.25 = -13.75 2.25 + 3x + x2 = -13.75 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = -13.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| (-12)(-10)= | | 15y+14=2(5y+6y) | | (16)(28)(2)= | | 5c-4c+c-3c= | | -3(5)(2)(-3)= | | 2.5x+50=80 | | 3a+(2a+6)= | | x/2+1=4-x | | x-.14(x)=250.00 | | 8b+8-4b-3= | | 5(4x-2)-5(3x-19)=2(2x+1)-1 | | x^2+-32x+220=0 | | 0.5(x+50)+0.5x=50 | | (-2)(6)(-5)= | | x-.14(x)=275.00 | | (-10)(-10)= | | 8p-9p=72 | | (-5)*(5)= | | -6p-9=-11-5p | | 3a+6+5a-2= | | -3x+(2x-3)= | | F=1/2(r+6.5) | | ln(3x-8)+ln(x-4)=2lnx | | p/8=20 | | 77=x+50 | | 16-5e=15.5 | | -(-2x-4)-x= | | 3a+6+5a-2 | | 22x-11=13x+7 | | x/7+x/9=16/63 | | 4+0.25r=6 | | a÷b-8=c÷d |